The Usability and Feasibility Testing of Tele-Heart Nursing Care/TNC a Digital Application for Preventing 30 Days Re-Admission Among Heart Failure Patients - Amalia, Irma Nur (Holistic Nursing Plus, 2025)
Background: An android-based application called ‘Tele-Heart Nursing Care’/TNC aims to assist remote monitoring for heart failure patients. By improving self-care through daily monitoring and efforts to increase adherence to therapy, it is expected to prevent 30-day readmission rates. Purpose: To test the usability and feasibility of the application by users, the System Usability Scale (SUS) was used, a standardized questionnaire that has been declared valid and reliable with a Cronbach Alpha value of 0.778. This stage of testing is a continuation of the previous testing by expert cardiologists, cardiac specialist nurses and IT experts. Methods: This study used quantitative methodology using SUS questionnaires to 10 heart failure patients at Dr M. Salamun Hospital Bandung in June 2024. Sampling with a cross-sectional approach with a minimum number to conduct testing. After patients accessed the TNC application then they filled out the SUS questionnaire. Results: From the ten questions in the SUS questionnaire, the average score of all respondents was 78.6 with a letter grade of B. The Tele-heart Nursing Care application can be used well by respondents, although there are still difficulties with the registration system, language use and other difficulties related to the use of applications related to the elderly. Conclusions: It can be concluded that the use of the Tele-heart Nursing Care Application can be used properly by respondents. And in the future, the use of TNC applications can be widely used in heart failure patients.